2013
DOI: 10.1088/1748-9326/8/3/034013
|View full text |Cite
|
Sign up to set email alerts
|

What day-ahead reserves are needed in electric grids with high levels of wind power?

Abstract: Day-ahead load and wind power forecasts provide useful information for operational decision making, but they are imperfect and forecast errors must be offset with operational reserves and balancing of (real time) energy. Procurement of these reserves is of great operational and financial importance in integrating large-scale wind power. We present a probabilistic method to determine net load forecast uncertainty for day-ahead wind and load forecasts. Our analysis uses data from two different electric grids in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…They found that the forecast uncertainty is greatest on days when the wind is forecast to be blowing strongly (see also [78]), thus there are some days when significant reserves are required, and other days when much smaller reserves are needed. When estimating the reserves that are needed to cover 95% of the dayahead forecast errors, [77] find reserve requirements substantially higher than those reported in many of the studies reviewed here. They suggest that a dynamic method should be used to schedule reserves, based on the day-ahead forecast values.…”
Section: Related Academic Studiescontrasting
confidence: 60%
See 1 more Smart Citation
“…They found that the forecast uncertainty is greatest on days when the wind is forecast to be blowing strongly (see also [78]), thus there are some days when significant reserves are required, and other days when much smaller reserves are needed. When estimating the reserves that are needed to cover 95% of the dayahead forecast errors, [77] find reserve requirements substantially higher than those reported in many of the studies reviewed here. They suggest that a dynamic method should be used to schedule reserves, based on the day-ahead forecast values.…”
Section: Related Academic Studiescontrasting
confidence: 60%
“…Several recent articles suggest, and apply, methods for quantifying costs associated with wind power variability. Mauch et al [77] estimated reserves requirements based on day-ahead load and wind forecast uncertainty. They found that the forecast uncertainty is greatest on days when the wind is forecast to be blowing strongly (see also [78]), thus there are some days when significant reserves are required, and other days when much smaller reserves are needed.…”
Section: Related Academic Studiesmentioning
confidence: 99%
“…11 is a simplified representation of electric power system operations that does not capture requirements for frequency regulation to ensure operating reliability (additional details are in SI Appendix, section S3). Furthermore, the model is fully deterministic, implying perfect foresight about the electricity demand and the variability of wind and solar energy resources and neglecting the effect of forecast errors on reserve requirements (25). In a system where variable renewable resources make up over 95% of the US energy supply, renewable energy forecast errors would be a significant source of uncertainty in the daily operation of power systems.…”
Section: Insufficient Power System Modelingmentioning
confidence: 99%
“…Reserve requirements also apply for EIMs and the costs for backup resources effect all market participants. There are various methods in practice to compute reserves [39,40,4]. The dominant approach is the n-sigma method, where reserves are calculated by assessing the standard deviation in generation and demand forecast.…”
Section: Reserve Schedulingmentioning
confidence: 99%